Design of Temperature Monitoring and Control System in Smart Hen Coop Based on Internet of Things - Parandy, La Mema; Hidayat, Sidiq Syamsul; Robby, Muhammad; Azhar, Rachael Al; Mujahidin, Irfan; Prabowo, M. Cahyo Ardi (Yayasan Gema Bina Nusantara, 2024)
Every temperature error detected by the system would be notified to users by the Blynk application, and the system would attempt to stabilize the temperature in hen coop with a lamp and fan. Notification from the Blynk application is set to stop until the temperature returns to an ideal. The Blynk application is equipped with a reset button to reset the chicken age counter. This system used temperature and humidity sensors DHT22 to sense the temperature, which the data from the sensor output read by Arduino Uno. The data that Arduino Uno reads is sent to NodeMCU. Afterward, NodeMCU sent the data to the Blynk server; therefore, the Blynk application displayed the temperature and humidity data on the Blynk dashboard. This system is expected to facilitate users/breeders in monitoring the temperature in the hen coop. Therefore, users/breeders do not need to worry about chickens dying due to heat or cold stress. The waterfall method is used in this design of the system. This system was tested in a 70 x 70 x 130 cm sized hen coop and entirely tested the system each minute for 35 minutes.